(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The study highlights the imperativeness of maintaining an effective customer service delivery by attacking the notorious problem of long queue in service industry especially in Union Bank Plc. The following were the objectives: to highlight the cause(s) of clumsy service delivery in this bank which is manifested in long queues, to ascertain the usefulness of queuing model in ameliorating this problem, To examine the effects of long queue and poor service delivery on the customers, To examine the measures put in place by the bank to ameliorate the problem of long queue, to ascertain the usefulness of supervision of the tellers and facilities in ensuring the efficiency and effectiveness service delivery. The paper adopted a survey method with questionnaire and oral interviews as instruments of getting the data. The analysis of the study was presented in simple percentage in a table. The population of the study was 118 for staff (Junior/senior) and the population of customers being infinite, a sample size was derived using Williams and Freud formula to get a total of 462 customers. The data collected were analyzed with descriptive statistics. The findings indicate that the long queue is caused by poor supervision of tellers and facilities. The long queue has caused a high rate of drop of their customers to other banks. The bank has tried to embark on many strategies to attack this problem but it came late after many customers had gone. The study concludes that customer satisfaction is of prime importance to any enterprise that wants to control a high share of the market for their products. As all banks sell the same products but each bank’s competitive advantage is its strategy for the satisfaction of her customers. Constant long queue in any service industry is an impediment to the realization of this goal. Proper supervision of queuing model is a panacea to this problem. The study recommends the following: proper and adequate supervision of tellers to maximize their efforts and show case the need for extra service points. There should be a constant appraisal of the staff to expose the trainable and un-trainable ones amongst them. The trainable ones should be sent for training while non-trainable ones will be laid off. There should be a proper examination of facilities and network system to keep them functional. Finally there should be regular promotional programmes to create the needed awareness to the public, informing them of the bank’s re-engineering of its system to attract them back to the bank.